Clinical utility of metagenomic next-generation sequencing in pathogen detection for lower respiratory tract infections and impact on clinical outcomes in southernmost China - Hao, Jinxiang; Li, Weili; Wang, Yaoyao; Zhao, Jiangman; Chen, Yu (Frontiers in Cellular and Infection Microbiology, 2023)
Background Today, metagenomic next-generation sequencing (mNGS) has emerged as a diagnostic tool for infections. However, since Hainan has a complicated pathogen spectrum, the diagnostic value and impact on patient outcomes of mNGS in Hainan are to be explored. Methods From April 2020 to October 2021, 266 suspected lower respiratory tract infections (LRTIs) patients in Hainan were enrolled, and specimens were collected before antibiotic treatment. Bronchoalveolar lavage fluid (BALF) samples were subjected to mNGS and culture to compare the diagnostic performance. Other conventional microbiological tests (CMT) were also performed. Patients’ treatments and clinical outcomes were recorded, and the antibiotic resistance genes (ARGs) were detected via mNGS workflow. Results The positive rate of mNGS outperformed that of culture (87.55% vs. 39.30%, p<0.001) and CMT (87.12% vs. 52.65%, p<0.001). Specifically, mNGS detected more P. aeruginosa (12.03% vs 9.02%, p<0.05), H. influenzae (9.77% vs 2.26%, p<0.001), Aspergillus fumigatus (3.00% vs 0.75%, p<0.05), Candida albicans (26.32% vs 7.52%, p<0.001) and uncommon pathogens. It also demonstrated great diagnostic advantages in Mycobacterium tuberculosis with 80% sensitivity and 97.4% specificity. Over half of the patients (147, 55.26%) had modified empirical treatment according to mNGS results and 89.12% of them responded well. For three deaths with modified treatment, multiple drug resistance was predicted by mNGS and confirmed by antibiotic susceptibility test. Conclusions The application of mNGS can benefit clinics in pathogen identification and antimicrobial treatment stewardship. Physicians should be alert to some emerging uncommon pathogens, including Chlamydia Psittaci, Nocardia otitidiscaviarum, and rare NTM.